Outcome of angiotensin receptor-neprilysin inhibitor on anxiety and depression in heart failure with reduced ejection fraction vs. heart failure with preserved ejection fraction - Jahanzeb Malik; Abdul Wahab Shahid; Mohsin Shah; Ghazanfar Rana; Ahmed Kamal; Hesham Naeem (Greater Baltimore Medical Center, 2021)
Objective: In patients with heart failure (HF), anxiety and depression are commonly observed and confer an adverse outcome. The first-in-class member of angiotensin receptor-neprilysin inhibitor (ARNI), sacubitril/valsartan has been demonstrated to improve functional class and decrease mortality in patients with heart failure with reduced ejection fraction (HFrEF) and reduce the readmission of heart failure with preserved ejection fraction (HFpEF). However, its effects on anxiety and depression levels remain unknown.Methods: Sacubitril/valsartan was started on 764 symptomatic patients with HFrEF and HFpEF who were receiving guideline-directed medical therapy (GDMT) with an angiotensin-converting enzyme inhibitor (ACEI) or angiotensin receptor blocker (ARB). Patients were evaluated using Hamilton's depression rating scale (HDRS) and the hospital anxiety and depression scale (HADS) for their levels of depression and anxiety before and after treatment at a six-month follow-up.Results: A significant reduction in HADS and HDRS scores was observed in patients with HFrEF (9.7 ± 1.3 to 6.4 ± 0.7, p = 0.032 and 19.2 ± 2.2 to 8.9 ± 1.6, p < 0.001, respectively) compared with HFpEF (p = 0.161 and 0.273, respectively). The six-minute walk test (6-MWT) significantly increased HFrEF from 195 ± 68 to 321 ± 97 (p < 0.001). There was an overall improvement in the functional class of all patients.Conclusion: Patients with HFrEF have the additional advantage of using sacubitril/valsartan in the form of decreased anxiety and depression symptoms in addition to an improvement in functional class. However, patients with HFpEF did not exhibit significant improvement in their psychological scores.